2015
DOI: 10.1177/0145445515615353
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Rural Environment Are Associated With Poor Oral Health Among Pregnant Women in Northern Appalachia

Abstract: Objectives Both oral health problems and depression among pregnant women contribute to maternal-infant health outcomes. Little is known, however, about the potential effects of clinically-significant depression on the oral health status of pregnant women. The purpose of the present study was to determine the influence of clinically-significant depression and rural- or urban-dwelling status on oral health outcomes among pregnant women. Materials and Methods Pregnant women (N=685) in rural (i.e., West Virginia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…Why people do not regularly attend dental services is complex, and there is probably an interplay between psychosocial, material, cultural and behavioural aspects as well as the perceived need for treatment. Factors found to be associated with less use of dental health services are lower socioeconomic status (SES), dental fear, distant geographic location and distance to dental care services and fatalistic beliefs …”
Section: Introductionmentioning
confidence: 99%
“…Why people do not regularly attend dental services is complex, and there is probably an interplay between psychosocial, material, cultural and behavioural aspects as well as the perceived need for treatment. Factors found to be associated with less use of dental health services are lower socioeconomic status (SES), dental fear, distant geographic location and distance to dental care services and fatalistic beliefs …”
Section: Introductionmentioning
confidence: 99%
“…Burt and Eklund, reflecting numerous studies, suggested there is less use of dental services by males, ethnic/racial minorities, those with lower education and those who lack dental insurance. Other investigations have suggested geographic location as an important factor . People who live in more rural areas, both adults and children, have comparatively worse oral health than their urban counterparts and may be less likely to utilize oral health care …”
Section: Introductionmentioning
confidence: 99%
“…Appalachia has one of the greatest burdens of oral health problems per capita in the USA and the lowest rates of dental utilization . More specifically, greater rates of caries and edentulism are found in Appalachia than in other regions of the USA . The desire for utilizing specialty oral health care (eg orthodontics) has been shown to be lower in Appalachia .…”
Section: Introductionmentioning
confidence: 99%
“…Additional work by the COHRA2 research team relates pregnant women's depression status to site differences [31], with possible clinical implications for dental practitioners.…”
Section: Discussionmentioning
confidence: 99%